THE EFFECT OF DISCOVERY LEARNING MODELS TO LEARNING OUTCOMES STUDENTS AND STUDENTS ACTIVITIES - Ihdi Shabrona Putri; Rita Juliani; Ilan Nia Lestari (Universitas Negeri Medan, 2017)
The aim of this study is to determine the effect of Discovery Learning to learning outcomes students on temperature and heat material. Research type is quasi experiment. The population in this research is all students of class X in SMA Negeri 20 Medan. The sample of the research is taken with class random sampling technique. In this study the measurements in the form of pretest to the subject and then treated with Discovery Learning models. The Instrument of this study was a learning result test and student activity observation sheet. The analysis result that there is a difference because effect of Discovery Learning models to learning outcomes students on temperature and heat material.